2019
DOI: 10.1111/1745-9125.12221
|View full text |Cite
|
Sign up to set email alerts
|

Sexual victimization against transgender women in prison: Consent and coercion in context

Abstract: In this article, we conjoin two long‐standing lines of inquiry in criminology—the study of prison life and the study of sexual assault—by using original qualitative and quantitative data from 315 transgender women incarcerated in 27 California men's prisons. In so doing, we advance an analysis of the factors and processes that shape their experience of sexual victimization in prison. The results of qualitative analysis of 198 reported incidents of sexual victimization exhibit a range of types of sexual victimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 72 publications
2
51
1
1
Order By: Relevance
“…The numerous women “going through the same thing” supported each other through the challenge. Like fighting, sexual relationships of any kind were forbidden by prison officials (Borchert, 2016; Gorga & Oehman, 2017; Jenness, Sexton, & Sumner, 2019), such that this form of embodiment also aligned with institutional rules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerous women “going through the same thing” supported each other through the challenge. Like fighting, sexual relationships of any kind were forbidden by prison officials (Borchert, 2016; Gorga & Oehman, 2017; Jenness, Sexton, & Sumner, 2019), such that this form of embodiment also aligned with institutional rules.…”
Section: Resultsmentioning
confidence: 99%
“…This was one of the most overt ways that prison officials used Protestant women to enforce institutional rules. Because all sexual relationships in prison are forbidden, reporting sexual activity could lead to punitive censure, including disciplinary tickets and solitary confinement (Borchert, 2016; Gorga & Oehman, 2017; Jenness et al., 2019). Aware of these possible outcomes, several Protestant women snitched to prison officials during one‐on‐one meetings with Chaplain Gibson, through anonymous notes dropped in the chaplain's mailbox, and via complaints to the warden.…”
Section: Resultsmentioning
confidence: 99%
“…3 This includes, for example, protective pairing-an institutionally derived coercive practice that involves "willingly" engaging in sexual exchanges with a prisoner in an effort to avoid being harmed by other prisoners (Oparah, 2010). This measure recognizes a range of types of sexual victimization and that consent in prison is a problematic concept (Jenness et al, 2019). During data collection, a team of eight interviewers traveled to 27 prisons for adult men in California and completed interviews with 315 transgender women.…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…Committing to the creation of more third (gendered, gender-neutral, or unisex) spaces (e.g., bathrooms, locker rooms, incarceration facilities, refugees, shelters) for individuals who do not wish to inhabit spaces with others of their sex along with more concerted efforts to enhance protections to better protect the privacy and safety of those who do (see Dolovich, 2011; Jenness et al, 2019 45 ). When possible (e.g., in a large facility) spaces might alternate between sexed and gendered spaces (e.g., bathrooms on different floors), with clear signs as to whether they are sex or gender separated.…”
Section: Alternatives To the Equality Act: Protecting Lgbt And Sex-bamentioning
confidence: 99%
“… 45. Interestingly, in their rich study of transwomen in men’s prisons in California, Jenness et al (2019) reported that most transwomen expressed a preference for housing in the men’s prison rather than the women’s prison. …”
mentioning
confidence: 99%